Perbandingan Kombinasi Putih Telur Rebus Dan Ikan Gabus Dengan Pemberian Ikan Gabus Terhadap Penyembuhan Luka Sectio Cesarea Pada Ibu Nifas Di Rumah Sakit Ridhoka Salma Cikarang Barat - Nurhayati Binti Syafrudin; Resi Galaupa (Jurnal Keperawatan Muhammadiyah, 2024)
Background: Maternal Mortality Rate (MMR) is a strategic indicator of health development that reflects the health status and quality of the population. The number of MMR in Indonesia in 2021 collected in the family health profile records at the Indonesian Ministry of Health still shows a high number of 7,389 deaths (RI Ministry of Health, 2022). Infection is one of the causes of maternal death, in developing countries at least one in ten maternal deaths is caused by infection. Postpartum wounds are still a common cause of infection in 80-90% of cases. Infections after childbirth are caused by normal birth wounds or caesarean section, mastitis, thrombophlebitis and pelvic inflammation. Objective: To determine the comparison of the combination of boiled egg white and snakehead fish with the administration of snakehead fish on the healing of cesarean section wounds in postpartum mothers. Methods: The design of this research is quantitative experimental research (quasi-experimental) with a "pretest posttest one group design. The sample in this study was all postpartum mothers with cesarean section wounds at the Ridhoka Salma Hospital, West Cikarang in December 2023 – January 2024 as many as 30 respondents. Results: Based on the research results, there is a comparison with the results of the T Test with a sig value of 0.029 < 0.05, which means Ha Accepted: There is a comparison of the combination of boiled egg white and snakehead fish with the administration of snakehead fish on the healing of cesarean section wounds in postpartum women at Ridhoka Salma Hospital Year 2024. Conclusions and Suggestions: There is a comparison of the combination of boiled egg whites and snakehead fish with the administration of snakehead fish on the healing of cesarean section wounds in postpartum women at Ridhoka Salma Hospital in 2024. It is hoped that the results of this research can become input material and can be applied in the field to provide animal nutrition for postpartum mothers, especially boiled egg whites and snakehead fish for healing cesarean section wounds.